Peningkatan Kreativitas Belajar Matematika Melalui Metode Stad Bagi Siswa Kelas III SDN Jenggolo 03 Kecamatan Margorejo Kabupaten Pati Tahun 2014/2015 - Noor Khusnul Khotimah, Siti; , Drs. Saring Marsudi, SH. M.Pd (2015)
Based on preliminary data on SDN Jenggolo 03 found various problems in learning Mathematics Fractions particular material in class III, among others, the lack of a sense of excitement, lack of like something from the other, the desire curiosity, like the heavier duty, active duty, the spirit asked. This causes the creativity of students learning to be low. The use of STAD method is an alternative solution to solve problems in mathematics teaching material fractions in class III. This study aimed to describe the increase in creativity studying Maths fractions material through STAD method in class III SDN Jenggolo 03 year 2014/2015. This research is qualitative research and design research is a class act that consists of 2 cycles. The first two meetings of the cycle and the second cycle of two meetings. This research was conducted in SDN Jenggolo 03, with a third- grade students study subjects with the number of 22 students, consisting of 14 girls and 8 boys and the object of this study is the creativity of student learning and STAD method. Data collection techniques by means of interviews, observation (observation), documentation, and field notes. The data analysis technique that is descriptive and percentage kualitatif.dengan pensekoran way. Based on the results of research and discussion, it can be concluded that there is an increase in the creativity of the third grade students of SDN Jenggolo 03 after following study using STAD, Improvement can be seen from the pre- stage cycle, the first cycle and cycle II. In the pre-stage cycle of creativity diketahuai low student learning with a percentage of 45%, the first cycle there is a slight increase in the percentage of students 55%, and the second cycle students' learning creativity very well with the percentage of 87%. This proves the increasing creativity of student learning using STAD method. So using STAD method can improve learning creativity Mathematics for Elementary School third grade students Jenggolo Margorejo Pati District 03 District of the Year 2014/2015